Hot punching for loading of biodegradable microcontainers with budesonide-Soluplus film. - Abid, Zarmeena; Andreoli, Francesca; Kristensen, Maja N.; Petersen, Ritika S.; Müllertz, Anette; Boisen, Anja; Keller, Stephan S. (Biomedical Microdevices, 2021)
Micro-reservoir based drug delivery systems have the potential to provide targeted drug release locally in the intestine, i.e. at the inflamed areas of the intestine of patients with inflammatory bowel disease (IBD). In this study, microcontainers with a diameter of 300 µm and a height of 100 µm, asymmetrical geometry and the possibility to provide unidirectional release, are fabricated in the biodegradable polymer poly-ɛ-caprolactone (PCL) using hot punching. As a first step towards local treatment of IBD, a novel method for loading of microcontainers with the corticosteroid budesonide is developed. For this purpose, a budesonide-Soluplus drug-polymer film is prepared by spin coating and loaded into the microcontainer reservoirs using hot punching. The processing parameters are optimized to achieve a complete loading of a large number of containers in a single step. A poly(lactic-co-glycolic acid) (PLGA) 50:50 lid is subsequently applied by spray coating. Solid-state characterization indicates that the drug is in an amorphous state in the drug-polymer films and the in vitro drug release profile showed a 68% release over 10 h. The results demonstrate that hot punching can be employed both as a production and loading method for PCL microcontainers with the perspective of local treatment of IBD.